White light intensities for maximum yield and quality of arugula microgreens - Mendes, Franciele Quintino [UNESP]; Purquerio, Luis Felipe Villani; Carvalho, Rogério Falleiros [UNESP]; Cecílio Filho, Arthur Bernardes [UNESP] (FapUNIFESP (SciELO), 2024)
The production of microgreens in plant factories is a great option for urban agriculture, and artificial light is one of the main factors for the success of this cultivation system. This study aimed to evaluate the effect of photosynthetic photon flux density (PPFD) (100, 200, 300, 400, 500 and 600 μmol m-2 s-1) of white LED on yield and quality of arugula microgreens. The experiment was conducted in an indoor environment, in a completely randomized experimental design, with six replicates. The highest yield was obtained with 358 μmol m-2 s-1, while 90 % of the maximum yield required 234 μmol m-2 s-1. The maximum shoot dry mass and cotyledon area were obtained with 439 and 312 μmol m-2 s-1, respectively, while the hypocotyl length decreased linearly with increasing PPFD. The highest nitrogen, phosphorus, calcium, sulfur and zinc contents were obtained with 380, 285, 326, 294 and 317 μmol m-2 s-1, respectively, while the maximum Fe content was obtained at the lowest light intensity. The contents of chlorophylls, carotenoids, phenolic compounds and antioxidant protection had maximum values with 600 μmol m-2 s-1, and the vitamin C with 458 μmol m-2 s-1.
Intensidades de luz branca para máxima produtividade e qualidade de rúcula microvegetal
Keywords: Eruca sativa; photosynthetic photon flux density; urban farm